Peroperative enteroscopy - Petroianu, Andy (São Paulo Medical Journal, 1997)
Current diagnostic alternatives for lesions of the small intestine are sometimes insufficient. Peroperative enteroscopy is presented as a useful method to identify and treat intestinal polyposis and angiodysplasias that can not be found by other methods. This technique was used on two patients. In both cases, this procedure was helpful and the appropriate treatment successfully completed.